Factors Associated with the Use of Intensity‐Modulated Radiotherapy for Head and Neck Cancer. (2nd September 2014) - Chen, Michelle M.; Roman, Sanziana A.; Sosa, Julie A.; Judson, Benjamin L.
Abstract : Objectives: (1) Describe temporal trends in the use of postoperative intensity‐modulated radiotherapy (IMRT) for head and neck cancer treatment. (2) Determine factors associated with the utilization of IMRT. Methods: A retrospective analysis of the National Cancer Database (2003‐2011) was used to identify 45, 154 adult head and neck cancer patients who had postoperative radiotherapy (RT) and to examine demographic, geographic, socioeconomic, and clinical characteristics. Our main outcome of interest was the receipt of IMRT. Statistical analysis included χ 2 tests, Student t tests, and multivariate regression. Results: From 2003 to 2011, the proportion of patients who had postoperative IMRT increased from 14.2% to 69.2%. Compared with those who had non‐IMRT, patients who had IMRT were more likely to be <55 years old (58.4% vs 66.7%, P <. 001), white (87.4% vs 89.6%, P <. 001), privately insured (45.5% vs 53.3%, P <. 001), in the West (15.6% vs 16.7%, P <. 001) or Midwest (25.8% vs 32.8%, P <. 001), and in receipt of concurrent chemotherapy (38.9% vs 60.5%, P <. 001). On multivariate analysis, private insurance, white race, Midwest and West locations, human papillomavirus positivity, concurrent chemotherapy, and academic centers were independently associated with the receipt of IMRT. Conclusions: IMRT has become the primary modality of delivery for postoperative RT in head and neck cancer patients. Results demonstrate racial, regional, and hospital‐level variation in the receipt of IMRT, suggesting heterogeneity in practice patterns across the United States.